1995
DOI: 10.1074/jbc.270.16.9558
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-10 Inhibits Nuclear Factor кB (NFкB) Activation in Human Monocytes

Abstract: Our previous studies in human monocytes have demonstrated that interleukin (IL)-10 inhibits lipopolysaccharide (LPS)-stimulated production of inflammatory cytokines, IL-1 beta, IL-6, IL-8, and tumor necrosis factor (TNF)-alpha by blocking gene transcription. Using electrophoretic mobility shift assays (EMSA), we now show that, in monocytes stimulated with LPS or TNF alpha, IL-10 inhibits nuclear stimulation of nuclear factor kappa B (NF kappa B), a transcription factor involved in the expression of inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
189
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(206 citation statements)
references
References 40 publications
13
189
3
1
Order By: Relevance
“…A NF-B binding site in murine IL-12p40 gene promoter region has been identified and is thought to play an important role in the regulation of IL-12p40 gene expression [35,36]. One earlier study has shown IL-10 to inhibit LPS-induced NF-B activation [33], however, a causal effect of IL-10 on NF-B activation and IL-12p40 gene transcription is not fully understood. One recent study showed that TGF-␤ inhibited IL-12p40 mRNA accumulation in LPS-stimulated peripheral human mononuclear cells, however, the mechanism of action of TGF-␤ on IL-12 production was not identified [37].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A NF-B binding site in murine IL-12p40 gene promoter region has been identified and is thought to play an important role in the regulation of IL-12p40 gene expression [35,36]. One earlier study has shown IL-10 to inhibit LPS-induced NF-B activation [33], however, a causal effect of IL-10 on NF-B activation and IL-12p40 gene transcription is not fully understood. One recent study showed that TGF-␤ inhibited IL-12p40 mRNA accumulation in LPS-stimulated peripheral human mononuclear cells, however, the mechanism of action of TGF-␤ on IL-12 production was not identified [37].…”
Section: Discussionmentioning
confidence: 97%
“…LPS activates a number of nuclear factors including NF-B, ets, AP-1, AP-2, GR, CREB, OCT-1, and Sp-1 [33,34]. A NF-B binding site in murine IL-12p40 gene promoter region has been identified and is thought to play an important role in the regulation of IL-12p40 gene expression [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-10 is a potent immunosuppressive molecule that can mediate the down-regulation of Th1 responses by inhibiting the production of IL-12, IFN-␥, and TNF-␣ (18). IL-10 is capable of inhibiting NF-B activation in human monocytes as well as IFN-␣-and IFN-␥-induced genes by suppressing tyrosine phosphorylation of STAT-1 (18,33,34). Studies with other alphaviruses have considered the expression of IL-10 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the inhibition of NF-B translocation to the nucleus with an inhibitory peptide was shown to decrease the upregulation of HLA-DR, as well as that of CD80, CD83, and CD86 (39). It has been shown that the inhibitory effect exerted by IL-10 and vitamin D 3 analogs on IL-12 synthesis depends on their capability to interfere with the NF-B pathway (39,40). FIG.…”
Section: Pka Mediates the Inhibitory Effects Exerted By 8-br-camp On Lpsmentioning
confidence: 99%